The magic screen : a history of regent street cinema (2015)
At the University of Westminster our vision for the future builds on our pro- gressive, inclusive and enterprising history, our roots as an innovative institu- tion with a social conscience, our early model – the original ‘Polytechnic’ blueprint – for collaborating with industry and practice, and our location in the heart of London. Our institution has played a leading role in the development and application of ‘film’ since the introduction of photography here in 1839, the creation of Europe’s first photographic studio in 1841 and the opening of our Photographic School in 1853.1 The ‘Home of Animated Photographs’2 – our Regent Street Cinema – was born here in 1896. Today, we are committed to providing ‘a vibrant global learning environment that inspires the next gener- ation of world citizens and helps to shape a better future for all’.3 The restored Cinema will significantly enhance this learning environment and attract a new generation of people to the University from London and across the globe. The reopening of our historic Regent Street Cinema in Spring 2015 was the exciting culmination of a programme of fundraising and renovation that began in 2009. The University’s Cinema Advisory Board, comprising staff and alumni and friends from the film industry, has worked with Tim Ronalds Architects to create an iconic facility for film screenings in which contempo- rary activities are unified within an historic space. We reached this landmark with the generous assistance of the Heritage Lottery Fund, The Quintin Hogg Trust and many other donors. To all who gave money, time and encourage- ment I offer a sincere ‘thank you’. Our newly restored Cinema supports our distinctive ambition to shape the future of professional life through the dynamic interaction of world- leading research, absorbing teaching informed by practice and enterprising education. These values enable our students to become global citizens, profess - ional leaders and lifelong learners, appreciating the need for interdisciplinary approaches in understanding and resolving the constantly evolving intellectual, professional and business challenges of the twenty-first century. Our alumni include many world names in film production and our academic staff in- clude leading documentary film makers and critical media analysts. The Regent Street Cinema and its associated facilities will further enhance our ability to have global impact and to attract international partners to London’s West End.